Investigation of Cten signalling and regulation in colorectal cancer - Akhlaq, Maham (2016)
Cten (also known as Tensin4) is the fourth member of the Tensin gene family. It lacks the N terminal actin binding domain while retaining the C terminal SH2 and PTB domains. This helps to bind Cten to the intracytoplasmic tail of β1 integrin and puts it at the heart of focal adhesions. It is reported to be a tumour suppressor in kidney and prostate cancer where normal tissues show high expression. However in a number of tumours, including colorectal cancer, Cten has been labelled as an oncogene. Cten which normally is a cytoplasmic protein gives nuclear staining in colorectal metastatic deposits. It increases motility, invasion and colony formation in colorectal cancer cells. In this study we have tried toexplore the mechanism of functional activity and regulation of Cten. We looked at Cten in the nucleus in vitro and identified new downstream binding targets. In addition we investigated the role of the SH2 domain of Cten concentrating on its downstream signalling molecules and binding partners. Furthermore, we explored regulators of Cten.